Can accreditation help a leopard change its spots?: Social accountability and stakeholder engagement in business schools. Issue 2 (7th February 2014) - Cooper, Stuart; Parkes, Carole; Blewitt, John
Abstract : Purpose: – Neo-institutional theory suggests that organisations change occurs when institutional contradictions, caused by exogenous and endogenous dynamics, increase over time to the point where change can no longer be resisted. Human praxis will result, but only when sufficiently powerful interests are motivated to act. This paper aims to examine the role that the accreditation of business schools can play in increasing institutional contradictions and hence fostering organisational change towards stakeholder engagement and engagement with social responsibility and sustainability issues. Numerous accreditations are promulgated within the higher education and business school contexts and a number of these relate to, or have aspects that relate to, ethics, social responsibility and sustainability. Design/methodology/approach: – The paper first analyses the take up of accreditations across UK business schools and then uses a case study to illustrate and explore stakeholder engagement and changes related to ethics, social responsibility and sustainability linked to accreditation processes. Findings: – Accreditations are found to be an increasingly common interest for UK business schools. Further, a number of these accreditations have evolved to incorporate issues related to ethics, social responsibility and sustainability that may cause institutional contradictions and may, therefore, have the potential to foster organisational change. Accreditation alone, however, is not sufficient and the authors find that sufficiently powerful interests need to be motivated to act and enable human praxis to affect change. Research limitations/implications: – This paper draws on previous research that considers the role of accreditation in fostering change that has also been carried out in healthcare organisations, public and professional bodies. Its findings stem from an individual case study and as such further research is required to explore whether these findings can be extended and apply more generally in business schools and universities in different contexts. Practical implications: – This paper concludes by recommending that the newly established UK & Ireland Chapter of PRME encourages and supports signatory schools to further embed ethics, social responsibility and sustainability into all aspects of university life in the UK. This also provides an opportunity to engage with the accrediting bodies in order to further support the inclusion of stakeholder engagement and issues related to this agenda in their processes. Originality/value: – This paper contributes by introducing accreditation as an institutional pressure that may lead indirectly to organisational change and supports this with new evidence from an illustrative case study. Further, it draws on the role of institutional contradictions and human praxis that engender organisational change.